Stakeholders prioritization of climate-smart agriculture interventions: Evaluation of a framework - Khatri-Chhetri, Arun; Pant, Anjali; Aggarwal, Pramod K.; Vasireddy, Vijya Vardhan; Yadav, Akhilesh (Elsevier, 2019)
This paper presents a framework to prioritize locally suitable climate-smart agricultural (CSA) interventions and implementation suitability assessments with key stakeholders: state and district agriculture departments, extension offices, agriculture research institutions, NGOs and donor agencies, private sector and farmers. Prioritization of appropriate interventions for given contexts is needed to assist relevant stakeholders to make strategic decisions and improve adaptability and efficiency of agriculture production system in the face of climate change and variability. First step includes participatory identification and evaluation of location specific CSA interventions suitable for different crop and cropping system with potential to reduce climatic risks in agriculture. All CSA interventions were evaluated based on their contribution to increase farm productivity and income, building resilience to changing climate and reduction of agricultural emissions. Second step includes evaluation of overall implementation feasibility of selected CSA interventions based on their technical feasibility, cost of implementation, inclusivity and synergy with current government programs. In the third step, potential barriers of CSA technology adoption were assessed linking with availability of resources, farmers' knowledge and acceptability, access to agriculture extensions service, market and government support. In the fourth step, incentive mechanisms to promote CSA interventions such as government subsidy, market linkage, provision of loan and capacity building were evaluated with farmers and key stakeholders. Finally, this prioritization framework assessed the role of different organizations such as the government, private sector, non-government organizations, custom hiring centers and community based organizations in promoting CSA interventions at the local level. Results show that this framework provides ample space for local stakeholders to integrate their knowledge and experience on CSA interventions in prioritization and investment planning. Stakeholders prioritized mainly water and nutrient management technologies, agriculture insurance against climatic risks and ICT based weather and agro-advisory services. This framework provides a decision support tool for policymaking in adaptation and mitigation activities in agriculture sector at the local level. This framework can be used by governments, development organizations and the private sector for investment decision-making.